2022
DOI: 10.3390/healthcare10020264
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Colorectal and Prostate Cancer Screening in a Large U.S. Health System

Abstract: During the first year of the coronavirus disease 2019 (COVID-19) pandemic, prevention measures included quarantining and facility closures. Because cancer screening is dependent on interventions in facilities, the extent of the COVID-19 impact on screening was questioned. A claims registry from a large health system was queried for colorectal and prostate cancer screening. A screening gap and screening loss ratio were calculated by comparing 2020 screening to historical reference years. All cancer screenings d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…43 In the United States, men and black people were disproportionately affected by decreased colorectal cancer screening, and to redress this deficit, it is estimated that rates of colorectal cancer screening need to increase by 50%. 42 Although many screening programs have resumed, the long-term impact of the pandemic on cancer screening and the prevalence of cancer as a result is not yet known. 41 A systematic review of the impact of the pandemic on colorectal cancer diagnosis and treatment, found a reduction in diagnosis and treatment, and that redressing the deficit requires strong and effective action to prevent negative consequences such as the number of people with advanced stages of cancer, potential increased treatment costs, quality of life and survival rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 In the United States, men and black people were disproportionately affected by decreased colorectal cancer screening, and to redress this deficit, it is estimated that rates of colorectal cancer screening need to increase by 50%. 42 Although many screening programs have resumed, the long-term impact of the pandemic on cancer screening and the prevalence of cancer as a result is not yet known. 41 A systematic review of the impact of the pandemic on colorectal cancer diagnosis and treatment, found a reduction in diagnosis and treatment, and that redressing the deficit requires strong and effective action to prevent negative consequences such as the number of people with advanced stages of cancer, potential increased treatment costs, quality of life and survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic negatively disrupted routine clinical care, with cancer programs such as screening no exception. Many programs were canceled or postponed, especially in 2020, a period of isolation measures such as lockdowns put in place to contain the spread of the virus 42 . These measures left people without access to recommended routine screening interventions, which were suggested to impact patients, healthcare professionals, and healthcare systems 43 .…”
Section: Discussionmentioning
confidence: 99%
“… 29 To catch-up to this backlog of screening colonoscopies, it has been estimated that the colonoscopy capacity should be expanded up to 150%. 30 Indeed, in the Netherlands, after the CRC screening halt, colonoscopy availability was expanded up to 120%, achieving a catch-up effect in the second part of 2020. 31 However, increasing the colonoscopy capacity is not possible for every health system, so it has been suggested that increasing FIT cutoff or using specific risk factors (male sex and advanced age) could be an effective strategy to prioritize access to colonoscopies and reduced the number of CRC or advanced adenomas underdiagnosed in a CRC screening program, compared with randomly reducing the number of population screened.…”
Section: Impact Of Covid-19 Pandemic In Crc Screeningmentioning
confidence: 99%
“…Evidence from hospital records or insurance claims have suggested that, compared to pre-pandemic levels, mammograms, pap smears and colonoscopies declined 60% to 90% in March/April 2020 (Duszak et al 2020;Bakouny et al 2021;Staib, Catlett, and DaCosta Byfield 2021. However, subsequent research has found that in the later months of 2020, claims and records of cancer screenings returned to pre-pandemic levels (Chen et al 2021); DeGroff et al 2021;Labaki et al 2021;McBain et al 2021;Bello, Chang, and Massarweh 2022;Drescher et al 2022). Still, the pandemic created a major cancer screening deficit which may be difficult to address despite recent investment in "return to screening" initiatives (Chen et al 2021;Hanna et al 2022;Kelkar et al 2022). Even as America returns to screening, some are being left behind (Mafi et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent research has found that in the later months of 2020, claims and records of cancer screenings returned to pre-pandemic levels (Chen et al 2021); DeGroff et al 2021; Labaki et al 2021; McBain et al 2021; Bello, Chang, and Massarweh 2022; Drescher et al 2022). Still, the pandemic created a major cancer screening deficit which may be difficult to address despite recent investment in “return to screening” initiatives (Chen et al 2021; Hanna et al 2022; Kelkar et al 2022). Even as America returns to screening, some are being left behind (Mafi et al 2022.…”
Section: Introductionmentioning
confidence: 99%